Efektifitas terapi hypnobirthing terhadap Kecemasan ibu hamil menanti kelahiran - Roziyani. S - -; Misrawati - -; Febriana - Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determined the effectiveness of hypnobirthing therapy  on maternal anxiety awaits birth. The design of this research was "Quasy experiment" by "Non-equivalent control group" respondents were divided into experiment group and control group. The research was conducted in the “Puskesmas Rumbai Pesisir Pekanbaru”. The total sample were 30 people who were taken by using purposive sampling techniques by noticing to the inclusion criteria. Measuring instrument that were used in both groups were questionnaires that have been tested for validity and realibility. Analysis used were univariate and bivariate analyzes using dependent and independent sample t test. The results showed there was significant decreasing in the rate of pregnant women anxiety with ρ (0.02) < α (0,05). It  means that hypnobirthing therapy is effective for decreasing the rate of anxiety in pregnant women. It is recommended in every public health care center have to prenatal class especially reguler hypnobirthing therapy. Keywords : hypnobirthing, anxiety